Detection of a diastolic heart sound in children and young adults using high-frame-rate echocardiography. (4th February 2022) - Mccrary, AW; Moore, C; Sturgeon, G; Lefevre, M; Kisslo, JA; Von Ramm, OT; Barker, PCA
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Colin"s Kids, Inc. PO Box 93 Hopewell, NJ 08525 Introduction: The auscultatory finding of a fourth heart sound (S4) is clinically associated with a pathologic decrease in left ventricular compliance, but may be seen in healthy children by phonocardiography. High-frame-rate difference imaging (HFRDI) has demonstrated several propagating myocardial phenomena in the left ventricular (LV) lateral wall throughout the cardiac cycle, including during diastole. We hypothesize that these visualized wave phenomena correlate with physiologic and pathologic heart sounds. Purpose: Using HFRDI, we sought to define the characteristics of a LV lateral wall late diastolic wave in healthy children and young adults. Methods: HFRDI was obtained from the apical 4-chamber view with synchronized electrocardiogram (ECG) on the T5 system (Phased Array Research Scanner) acquiring images for this study between 587 and 1174 frames per second (depending on participant imaging characteristics). In addition, tissue Doppler images were acquired with synchronized ECG and phonocardiography (PCG) on a commercial ultrasound machine (Figure 1). Timing events were measured from the QRS onset on the ECG tracing. An S4 wave correlate was defined by meeting the following criteria: 1) occurring after the P wave on ECG; 2) at or after the onset of a' on TDI; 3) occurring during the PCG S4; and 4) occurring prior to the S1 wave complex. The timing of the S4 wave in HFRDI was measured from the onset of QRS to the first appearance of the wave, and the wave velocity was calculated by measuring the length of the lateral wall and counting temporally calibrated image frames while the wave was visible. Results: Nine healthy volunteers completed the imaging protocol with a median age of 20 years (range 6 – 22 years). A single, distinct late diastolic HFRDI wave was seen in all participants propagating from apex to base of the lateral LV free wall. This wave met the defined criteria to be a visual correlate of S4 in all participants. Measurements of correlated events are presented in Table 1. S4 propagating velocity was 2.96 ± 1.8 m/sec and occurred 25 ± 18 msec prior to the QRS onset. There is a strong positive correlation between age and S4 velocity [r(7) = 0.76, p = 0.019]. Conclusion: The S4 heart sound can be reliably visualized by high frame rate imaging and has similar characteristics in healthy children and young adults. Further definition of normal and abnormal S4 wave characteristics may lead to a novel tool in defining LV diastolic function.